ChemInform Abstract: Palladium‐Catalyzed [4 + 2] Cycloaddition of Aldimines and 1, 4‐Dipolar Equivalents via Amphiphilic Allylation. Issue 25 (5th June 2015) - Hirata, Goki; Yamada, Naoshi; Sanada, Shohei; Onodera, Gen; Kimura, Masanari
Abstract: The title reaction is promoted by diethylzinc.